Study of perioperative factors in postoperative chronicity of sternal pain - Yadav, Lokesh; Sharma, Praman; Ansari, Afroz; Paudyal, Nabin (Nepal Medical College Journal, 2023)
Over two million people undergo sternotomy worldwide for heart surgery each year, and post operative sternal pain may last for months or reappears a long time after sternotomy. The exact etiology of post sternotomy pain is unknown. We aim to find out the association of peri-operative factors with chronicity of sternal pain after open-heart surgery. This is a retrospective observational study on 121 patients who underwent open heart surgeries for various cardiac problems from January 2020 to July 2022 at a tertiary care center. Convenient sampling was performed. Data were analyzed using SPSS-17. Male to female ratio similar with male 60 (49.6%) and female 61 (50.4%), and 95.0% had body mass index (kg/m2) <30. Ninety (76.9%) were individuals without diabetes, 75 (62.0%) were non-hypertensive, 97 (80.2%) were nonsmokers and 22 (18.2%) had abnormal thyroid function. Only 2 (1.7%) had chronic obstructive airway disease and 1 (0.8%) had renal failure. Majority was in sinus rhythm 88 (72.7). Forty (33.1%) had valvular and 53 (43.8%) had ischemic etiology. Majority 110 (90.9%) were ventilated for less than 6 hours and 15 (9.4%) had surgical site infection. Peri-operative risk factors like age of patient, etiology, hypertension, operative procedure, ventilator hours, cardiopulmonary bypass time, intensive care unit stay, and total hospital stay had a significant association with chronicity of pain.